Pemenuhan Hak Dan Kewajiban Franchisor Dalam Pembinaan Usaha Terhadap Bisnis Waralaba (Franchise) Perspektif Wahbah Az-Zuhaili : (Studi Kasus Kecamatan Medan Kota Kota Medan) - Nabila Zahra Siregar; Mustapa Khamal Rokan; Rahmat Hidayat (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
Franchising is part of a type of syirkah where there is a partnership association and raising funds as well as the use of trademarks. This also requires the franchisor to provide rights to the franchisee in the form of scientific, marketing and administrative rights to manage the business. This obligation was apparently not carried out by the Dimsum 1000 franchise, where all obligations to provide marketing knowledge were not carried out by the franchise. In writing this essay, the author formulates a problem in the form of how to implement the Dimsum 1000 franchise business in Medan District, Medan City? How do franchisors fulfill their rights and obligations in developing the Dimsum 1000 franchise business in Medan District, Medan City? How do you fulfill the rights and obligations of the Dimsum 1000 franchise business from Wahbah Az-Zuhaili's perspective in Medan District, Medan City? In this research the author uses empirical legal research. The results of the research explain that the implementation of the Dimsum 1000 franchise business in Medan District, Medan City, goes through a business cooperation agreement procedure first. Then all the equipment for selling is provided by Dimsum 1000. However, in the marketing strategy Dimsum 1000 is considered old-fashioned and out of date. Fulfillment of the franchisor's rights and obligations in developing the Dimsum 1000 franchise business in Medan City District. Medan City does not fulfill the franchisee's rights in the form of guidance in the form of training, management operational guidance, marketing, research and development for franchisees on an ongoing basis. Fulfillment the rights and obligations of the Dimsum 1000 franchise business from Wahbah Az-Zuhaili's perspective in Medan City District, Medan City, did not happen at all. Dimsum 1000 franchise practices viewed from Wahbah Az-Zuhaili's perspective are not in accordance with the fulfillment of the concept of rights applied in Wahbah Az-Zuhaili's own view. This can be seen from not providing guidance in the form of training, operational management guidance, marketing, research and development to franchisees on an ongoing basis, which violates the rights of the franchisees themselves.